THE SYSTEM OF COST MANAGEMENT OF HAJJ ACCORDING TO THE PERSPECTIVE POSITIVE LAW IN INDONESIA - ,SH, Burhanudin (Jurnal IUS (Kajian Hukum dan Keadilan), 2014)
Regulation of Hajj is regulated in Act Number 13/2008 on Implementation of Hajj. Legal certainty for Indonesian citizens who want to carry out the pilgrimage to the holy land of Mecca is organized by hajj organizers and management systems. Legislation approach (Statute Approach) is conducted by reviewing all laws and regulations cost management of hajj, while Conceptual Approach is examines the views / draft experts regarding the Cost Management of hajj. According to the positive law, cost management of hajj are based on Act Number 13/2008 on Management of Hajj, Minister of Religion Regulation Number 10/2005 and Minister of Religion Decision Number 396/2003 on Management of Hajj, stated that cost management of hajj are manage by The Minister of Religion in cooperation with the Sharia Bank and conventional bank that accountable to President and Parliament. However, the cost management of hajj is not provide benefits to the principle of Indonesian pilgrims. From the nine principle of good governance, there are three principles that implemented, which are principle of participation, responsiveness, and principle of consumers oriented. The other six principles that have not done are the principle rule of law, transparency, fairness, efficiency, accountability and strategic vision principle. The ideal cost management of hajj in the future is by using the management system that directly, fast and transparent (DFT).Keyword: Cost Management of hajj, Positive Law